Women on Welfare: A Macroeconomic Analysis - Greenwood, Jeremy; Guner, Nezih; Knowles, John A (American Economic Review, 2000)
Look at the dramatic change in family structure that has occurred recently, illustrated in Figure 1. In the United States, 23 percent of children lived with an unwed mother in 1998, compared with only 8 percent in 1960.1 Of this 15-percentage-point increase, about 6 percentage points are due to a rise in the rate of divorce; the remaining 9 percentage points arise from an increase in out-of-wedlock births. Why care about this change in the structure of families? The lot of children living with a single mother is bleak. About 70 percent of those children in a family with a never-married mother were living near or below the poverty level in 1995. The corresponding figure for children being raised by a divorced mother was 45 percent. Associated with the increase in number of single mothers has been a rise in the percentage of the population on welfare. In 1960 only 1.7 percent of the population was on AFDC (Aid to Families with Dependent Children), while in 1995 about 5.2 percent were. Most mothers who received AFDC were single; 71 percent were in 1993. Also, AFDC mothers tended to have more children (2.6 on average vs. 2.1 for the population as a whole in 1993). It is interesting to note that there is evidence suggesting that more entrances into and exits out of welfare are connected with a shift in family structure rather than with a change in employment status. For instance, of the first-time entrances into welfare during 1983-1991 about 21 percent were associated with an out-of-wedlock birth, 23 percent were connected with a divorce or separation and 21 percent were linked with a reduction in the mother's work hours. Last, real AFDC benefits rose by about 70 percent between 1945 and 1977. They were about 25-percent higher in 1995 than in 1945. Could this have contributed to the rise in single motherhood? The task here is to outline a general-equilibrium model in which, at any point in time, some individuals will marry, others will divorce, and yet others will choose to have out-of-wedlock births. While the model is still prototypical in nature, it will be shown how such a framework can be used to address public-policy questions, in particular, the impact of welfare on family structure and the well-being of the economy.